Microscopic Polyangiitis With Positive Hantaan Virus-Specific Immunoglobuline M Antibody Caused by Cross Reaction: A Case Report - Diao ZONGLI,; Zhang AIHUA,; Wang GANG,; Liu WENHU, (Archives of Rheumatology, 2015)
Patients with microscopic polyangiitis may have an immune disorder and generate antibodies which may cross-react with foreign proteins. In this article, we report a 71-year-old female case of microscopic polyangiitis patient with positive Hantaan virus-specific immunoglobuline M antibodies without hemorrhagic fever with renal syndrome. In this case, an immune disorder may generate antibodies that cross-reacting with Hantaan virus antigen, resulting in positive Hantaan virus-specific immunoglobuline M antibody measurements.